Vasculitides and occluding vasculopathies, challenges in recognizing histopathological patterns, and their solutions - Wilk, Michael; Zelger, Bettina G.; Zelger, Bernhard (Frontiers in Medicine, 2023)
Previous classifications of vasculitides and occluding vasculopathies including most important and mainly coagulopathies may have impediments. First, classifications may follow different principles including clinicopathologic findings, etiology, pathogenesis, prognosis, or therapeutic options. Second, some authors fail to distinguish between vasculitis and coagulopathy which is crucial because of differences in pathogenesis, therapeutic consequences and prognosis. Third, vasculitides and occluding vasculopathies are systemic diseases. Organ-specific variations make morphologic findings difficult to compare. Fourth, subtle changes are recognized in the skin, but may be asymptomatic in other organs. Our aim is to use the skin and subcutis as a model and the clinicopathological correlation as the basic process for classification. We use an algorithmic approach with pattern analysis, which allows consistent reporting of microscopic findings. We first differentiate between small and medium vessel vasculitis. Secondly, we differentiate the subtypes of small and medium-sized vessels. Finally, we differentiate vasculitides according to the predominant cell type into leukocytoclastic and/or granulomatous vasculitis. Regarding leukocytoclastic vasculitis as a central reaction pattern of cutaneous small/medium vessel vasculitides, its relation or variations may be arranged around like spokes of a wheel which may aid to establish some basic order in this complex realm of cutaneous vasculitides. With respect to occluding vasculopathies the first two steps are identical to the algorithm of vasculitides, and we finally differentiate according to the time point of the coagulation/reorganization process and the involved inflammatory cells/stromal features. By visualizing the criteria in the style of bar codes, clinical and histological overlaps and differences become more transparent.